Residue of Tetracyclineand Penicillinn Antibiotic On Pork In Denpasar Bali - Siswanto Siswanto; I Nyoman Sulabda (Institute for Research and Community Service, Udayana University, 2019)
Humans need food from animals in quantity and good quality, so that the needs of the body are fulfilled. Meat products such as pork can contain certain ingredients such as antibiotic residues that have a negative impact on health. Monitoring antibiotic residues in pork must be carried out periodically to prevent and be aware of antibitics. Survey research on antibiotic residues in pork marketed in Denpasar, Bali. The goal is to find out tetracycline and penicilline antibiotic residues in pork which are marketed in Denpasar, Bali, Indonesia. Fifty pork samples from Badung, West Denpasar, East Denpasar, North Denpasar and South Denpasar markets. Each market is taken 10 samples purchased from different traders. Each weight is 100 grams. Antibiotic residue testing was carried out qualitatively using a screening test method.